HTLV-1 Alters T Cells for Viral Persistence and Transmission - Tanaka, Azusa; Matsuoka, Masao (Frontiers in Microbiology, 2018)
Human T-cell leukemia virus type 1 (HTLV-1) was the first retrovirus to be discovered as a causative agent of adult T-cell leukemia-lymphoma (ATL) and chronic inflammatory diseases. Two viral factors, Tax and HTLV-1 bZIP factor (HBZ), are thought to be involved in the leukemogenesis of ATL. Tax expression is frequently lost due to DNA methylation in the promoter region, genetic changes to the tax gene, and deletion of the 5' long terminal repeat (LTR) in approximately half of all ATL cases. On the other hand, HBZ is expressed in all ATL cases. HBZ is known to function in both protein form and mRNA form, and both forms play an important role in the oncogenic process of HTLV-1. HBZ protein has a variety of functions, including the suppression of apoptosis, the promotion of proliferation, and the impairment of anti-viral activity, through the interaction with several host cellular proteins including p300/CBP, Foxp3, and Foxo3a. These functions dramatically modify the transcriptional profiling of host T cells. HBZ mRNA also promotes T cell proliferation and viability. HBZ changes infected T cells to CCR4+TIGIT+CD4+ effector/memory T cells. This unique immunophenotype enables T cells to migrate into various organs and tissues and to survive in vivo. In this review, we summarize how HBZ hijacks the transcriptional networks and immune systems of host T cells to contribute to HTLV-1 pathogenesis on the basis of recent new findings about HBZ and tax.